2012
DOI: 10.1097/rhu.0b013e31825828be
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Periodontal Disease Hampers Anti–Tumor Necrosis Factor Treatment Response in Rheumatoid Arthritis

Abstract: This study supports the notion that PD may affect TNF blocker efficacy in patients with RA. The possibility that a sustained gingival inflammatory state may hamper treatment response in this disease has high clinical interest because this is a treatable condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 39 publications
3
72
0
14
Order By: Relevance
“…31,32 The human microbiome plays important roles in immune regulation and self-tolerance. 33 Disturbance of the intestinal microbiome has been linked to several autoimmune diseases, including IBD, 34,35 rheumatoid arthritis, [36][37][38][39][40] and at least 1 category of JIA. 14 After antibiotic treatment, commensal microbial populations often recover within ∼3 months, including in young children.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 The human microbiome plays important roles in immune regulation and self-tolerance. 33 Disturbance of the intestinal microbiome has been linked to several autoimmune diseases, including IBD, 34,35 rheumatoid arthritis, [36][37][38][39][40] and at least 1 category of JIA. 14 After antibiotic treatment, commensal microbial populations often recover within ∼3 months, including in young children.…”
Section: Discussionmentioning
confidence: 99%
“…These fi ndings have been independently validated in populations from different geographic regions [ 38 -41 ]. In a more recent prospective study on RA patients initiating anti-TNF treatment, it was shown that the presence of persistent PD hampered the clinical response to TNFi, since only those patients without established PD achieved good RA outcomes [ 42 ].…”
Section: Background On Pd Treatment As Adjuvant For Ra Clinical Outcomesmentioning
confidence: 99%
“…[108][109][110] The presence of periodontitis is also shown to hamper RA treatment with TNF-a blockers. 111 The periodontal bacterium P gingivalis is unique among the oral flora because it possesses an enzyme needed for protein citrullination, a major hallmark of RA. 109 Therefore, it would follow logically that reduction of the P gingivalis level and inflammation levels via periodontal treatment should decrease the severity of RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%